Assessment of biorational insecticides to control thrips colonizing lettuce in greenhouse - Diaz, Beatriz Maria; Puhl, Laura Elena; Castresana, Jorge Eduardo (Ediciones INTA, 2025)
Thrips is one of the key lettuce pests that reduce yield and quality by direct damage caused mainly by piercing-sucking feeding and indirect damage by virus transmission. Conventional management of thrips is based on a few active ingredients of synthetic insecticides at the risk of generating resistance and environmental disruption. Currently, a new generation of insecticides of botanical origin and other natural derivatives are available on the market. The aim of this study was to evaluate the efficacy of biorational insecticides against thrips and their impact on natural enemies and lettuce production in a greenhouse. The assays were carried out in a greenhouse at INTA Concordia, Argentina during the autumn of 2022 and 2023. Three biorational insecticides were tested by contact: the positive control, azadirachtina (Neemazal® 1,2% EC, 0,4%), potassium oleate (Hydralene® AGK 48% SC, 2%), orange essential oil (OEO 10% SC, 0,3%), and additionally, water was included as a negative control. Applications began when thrips populations reached the economic injury threshold according to lettuce phenology. Thrips population and their natural enemies were inspected weekly on plants and after the first application also on yellow and blue sticky traps. Lettuce yield and losses were evaluated for each treatment at harvest. Neemazal® was the most effective bioinsecticide to reduce thrips infestation (42-53%), followed by Hydralene® (27-37%). No evident effect was obtained with the experimental OEO (0-19%). The reduction of the thrips infestation was directly related to their direct damage and inversely related to the crop losses (5-11%). No significant effects on natural enemies captured by sticky traps were observed, with the exception of ladybugs in the OEO treatment. Mode of action and the possibilities to include bioinsecticides in an IPM program are discussed.